Charter and Ordinances of the City of La Crosse, with the Rules of the Common Council, at 239-242, Ordinance no. 37 (1888) - (:unkn) unknown (My University, 1881)
It shall be unlawful for any person to keep for sale, sell or give away any gunpowder, giant powder, nitro-glycerine, gun-cotton, dynamite or any other explosive substance of like nature or use without having first obtained a license therefor from the city of La Crosse in the manner hereinafter provided. Any person convicted of a violation of this section shall be punished by a fine of twenty-five dollars for each offense.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER